PLAN ESTRATÉGICO DE MARKETING PARA PROMOCIONAR EL TURISMO SOSTENIBLE EN LA FINCA ZAMORA, CANTÓN BUENA FE, PROVINCIA DE LOS RÍOS - Ortiz HIdalgo, Renato Israel (2022)
The present research work was carried out in the Buena Fe Canton, Los Ríos Province in order to analyze how sustainable tourism influences Finca Zamora, this research has as its main objective to promote sustainable tourism through a strategic marketing plan. using different techniques and methods, which later these will serve to promote sustainable tourism and also favoring a greater economic income to the sector. In order to analyze how Finca Zamora influences residents and tourists, a 10-question survey was carried out quantitatively to 382 residents and tourists, thus obtaining clear information on what should be improved in the sector. According to the results we obtained from the survey, the residents and tourists determine that Finca Zamora is not currently considered as a tourist potential, this is due to the scarcity of tourists in the Finca and also due to the lack of new strategies to attract more tourists and residents.